Derrame Pericárdico Recidivante. Um Caso de Angiosarcoma Cardíaco - Marcão, I (2001)
A case of angiosarcoma of the right atrium in a 59-year-old woman is reported, presenting as a recurrent hematic pericardial effusion. The usefulness of echocardiography in making the diagnosis is emphasized. The tumor was already disseminated at the time of the diagnosis. The patient was on palliative therapy, dying a few months later. The histological examination was done at autopsy. This case highlights the difficulty in diagnosis and the various modalities available for an accurate diagnosis of a rare clinical entity. It has a rapid and aggressive course with a very poor prognosis.